Dynamic behaviour of seismically isolated cylindrical offshore storage tanks - Mastanzade, Nijat; YAZICI, GÖKHAN (AMER SOC MECHANICAL ENGINEERS, THREE PARK AVENUE, NEW YORK, NY 10016-5990 USA, 2005)
Cylindrical offshore storage tanks are mainly used to store critical liquids such as petroleum and LNG. Failure of these tanks after an earthquake not only results in high financial losses but can also create an environmental disaster as well. Seismic isolation technique has been utilized in this study to mitigate the damaging effects of lateral earthquake forces. In this study, seismic isolation is used in cylindrical offshore storage tanks. Seismic isolators are protected from the marine environment by a water-proof flexible membrane that allows the horizontal movement of the tank. The mathematical model takes the following into account: mass of the stored liquid, added mass of the water surrounding the tank, horizontal stiffness and damping of the isolation system. Internal forces due to the hydrostatic and hydrodynamic forces acting on the system during an earthquake have been calculated by using the shell-moment theory. The results of the analyses are compared for both the isolated and fixed-base tanks.
Keywords: liquid storage tanks; seismic isolation; sıvı depolama tankları; sismik izolasyon